2016
DOI: 10.1007/s10439-016-1605-7
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of a Tissue-Engineered Tubular Heart Valve in Growing Lambs

Abstract: Current pediatric heart valve replacement options are suboptimal because they are incapable of somatic growth. Thus, children typically have multiple surgeries to replace outgrown valves. In this study, we present the in vivo function and growth potential of our tissue-engineered pediatric tubular valve. The valves were fabricated by sewing two decellularized engineered tissue tubes together in a prescribed pattern using degradable sutures and subsequently implanted into the main pulmonary artery of growing la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
114
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(123 citation statements)
references
References 25 publications
(46 reference statements)
5
114
3
Order By: Relevance
“…Although this reduction in elastin may affect the mechanical parameters of the NAC and will be evaluated in future studies, this was an expected outcome of the detergent-based decellularization process. Elastin has been shown in previous studies to be significantly decreased during decellularization in a variety of tissue types (Petersen, Calle et al 2012, Reimer, Syedain et al 2016). However, it has also been observed that the native environment in vivo can restore levels of elastin and other extracellular proteins, such as collagens, after scaffolds are reincorporated into the body (Ghazanfari, Driessen-Mol et al 2015, Reimer, Syedain et al 2016).…”
Section: Discussionmentioning
confidence: 82%
“…Although this reduction in elastin may affect the mechanical parameters of the NAC and will be evaluated in future studies, this was an expected outcome of the detergent-based decellularization process. Elastin has been shown in previous studies to be significantly decreased during decellularization in a variety of tissue types (Petersen, Calle et al 2012, Reimer, Syedain et al 2016). However, it has also been observed that the native environment in vivo can restore levels of elastin and other extracellular proteins, such as collagens, after scaffolds are reincorporated into the body (Ghazanfari, Driessen-Mol et al 2015, Reimer, Syedain et al 2016).…”
Section: Discussionmentioning
confidence: 82%
“…Several previous preclinical studies have demonstrated that remodeling of TEHVs does not naturally lead to a desired outcome (11,12,15,17,18,(20)(21)(22). Consequently, because of the strong interdependency of mechanics and tissue remodeling, mechanical models that can predict the relevant biological mechanisms are extremely valuable in understanding the adaptation of engineered cardiovascular tissues and proposing solutions for how to improve their performance.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, in situ TE concepts relying on the recipient's body to regenerate the implant in vivo represent the most advanced and clinically relevant methodology. In particular, tissue-engineered extracellular matrices (ECMs) depleted of cells have proven to be a valid off-the-shelf alternative to the initially described in vitro TE approaches in several preclinical investigations (11,12,15,18,22). Furthermore, the principal feasibility of implanting biodegradable polymeric scaffolds in a preclinical animal model, which are transformed into cell-repopulated valves in vivo, has been recently demonstrated (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the work of Kang et al employs a more basic science framework to study cell viability, their optimization of crosslinking conditions during the encapsulation of cells is a necessary step in the assessment of hydrogels as a viable scaffold material for tissue engineered heart valves (TEHVs) The articles by Picard-Deland et al and Reimer et al both focus on tubular heart valves. 11,12 Tissue engineered tubular heart valves are emerging as an attractive approach with potential for growth-a characteristic critical for pediatric applications. These two papers offer contrasting approaches to combat the major hurdle of post-implantation activation of valve cells within the TEHV and subsequent contraction of the engineered tissue.…”
mentioning
confidence: 99%